PENGARUH PARTISIPASI ANGGARAN, TINGKAT KESULITAN SASARAN ANGGARAN, DAN EVALUASI ANGGARAN TERHADAP TINGKAT REALISASI ANGGARAN PENERIMAAN PAJAK BUMI DAN BANGUNAN - Drs. Ec. K Soetanto Warsoko, MM (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
Budgeting is an element of management controll system that works as planning device. Budgeting is accepted as key element in the system of planning and controlling. The purpose of the study is know the influence of budgeting arrangement participation, the difficulty degree of budgeting objectives and budgeting evaluation to the realization degree of budgeting revenue from tax of land and construction/Pajak Bumi dan Bangunan. Samples of the study are KP PBB Kanwil XI DJP East Java with 8 (eight) number of KP PBB that consist of KP PBB Surabaya I, Surabaya, II, Surabaya III, Gresik, Bojonegoro, Pamekasan, Madiun, Ngawi. Data analysis for this study using miltiple regression. The results of this study shows that variation pattern the changes variables of budgeting arrangement participation, the difficulty degree of budgeting objectives and budgeting evaluation explains contribution the influence variable of realization degree of budgeting revenue from land and construction/Pajak Bumi dan Bangunan in the amount of 38,9% (R-square).